Akad Jual Beli Saham Lewat Online Studi Komparatif Ulama Mazhab Syafi’i dan Dewan Syariah Nasional - Safri, Muhammad; Has, Nisaul Haq Bintu (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This article aims to find out the contracts used in general stock buying and selling transactions and buying and selling contracts through online media according to the views of the scholars of the Shafi’i school and the views of the National Sharia Council. The type of research in this article is library research, the approach used is a normative-juridical approach. In conducting stock buying and selling transactions online, there are parties who make transactions even though they do not know each other, and in the transaction there is no sale and purchase contract except only in an agreement on the amount to be purchased and the price offere. In the view of the Shafi’i school, buying and selling transactions must meet the elements of the pillars, one of which is the existence of sighat between the seller and the buyer. However, there are also scholars of the Shafi’i school that still allow buying and selling transactions even though there is no sighat in them based on the urf that has been applied in society. Meanwhile, the National Sharia Council in its fatwa allows the public to carry out share buying and selling transactions because shares are a form of cooperation between one party and another in terms of seeking mutual benefits